Kiai Leadership Values at the Paciran Lamongan Muhammadiyah Modern Islamic Boarding School - Arzi Shafaunnida; Amir Bandar Abdul Majid; Nurchamidah; Baso Syafaruddin; Muhammad Hamsah (al-Afkar, Journal For Islamic Studies, 2024)
Indonesia has many Islamic boarding schools, but very few Islamic boarding schools implement the cultivation of leadership character values, in this case dominated by the role of Kiai as a whole. The Paciran Lamongan Muhammadiyah Islamic Boarding School is one of the boarding schools that applies leadership character values to its students. The method used in this research is a qualitative method using a phenomenological perspective. The results of the research revealed that values were developed from the role of the figure of Kiai who emphasized the morals of Rasulullah SAW taught to students such as shiddiq, amanah, tabligh and fathonah to be continued into the personality of the students to become leaders of the community. Kiai's role in instilling leadership values in students is that he places his position not only as a caregiver but also as an advisor, educator, mobilizer, figure, coordinator and facilitator to foster the values of humility and sincerity.